Positive electrode active material for nonaqueous electrolyte secondary batteries, method for producing positive electrode active material for nonaqueous electrolyte

By using lithium transition metal composite oxide with a layered structure in a nonaqueous electrolyte secondary battery and combining Ca and Sr compounds to protect its surface, the problem of structural damage and capacity reduction of lithium transition metal composite oxide with high Ni content is solved, and high capacity and improved charge and discharge cycle characteristics are achieved.

CN119650677APending Publication Date: 2025-03-18PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411631017.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-11-29
Filing Date
2020-09-17
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In nonaqueous electrolyte secondary batteries, the lithium transition metal composite oxide with high Ni content is captured in large amounts during charging, resulting in damage to the layered crystal structure and reduced capacity, and the charge and discharge cycle characteristics still need to be improved.

Method used

A lithium transition metal composite oxide having a layered structure is used, the general formula is LiaNixMnyMzO2-b, wherein M is at least one element selected from Al, Co, Fe, Ti, Si, Nb, Mo, W and Zn. The surface is protected by a Ca and Sr compound, and the structure is adjusted below 850°C through a calcining process.

Benefits of technology

The reduction of battery capacity is effectively suppressed, the charge and discharge cycle characteristics are improved, the structural stability of lithium transition metal composite oxide is maintained, and the erosion of the structural deterioration layer is reduced through surface protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650677A_ABST
    Figure CN119650677A_ABST
Patent Text Reader

Abstract

A positive electrode active material for a non-aqueous electrolyte secondary battery, a method for producing the positive electrode active material for a non-aqueous electrolyte secondary battery, and a non-aqueous electrolyte secondary battery. The positive electrode active material for a nonaqueous electrolyte secondary battery includes: a predetermined lithium transition metal composite oxide having a layered structure; and a compound (A) that is present on the surface or grain boundary of the primary particles of the lithium transition metal composite oxide and contains Ca and / or Sr. The layered structure includes a Li layer in which Li reversibly enters and exits, and the proportion of metal elements other than Li present in the Li layer is 0.7-3.0 mol% with respect to the total molar amount of the metal elements other than Li in the lithium transition metal composite oxide. The ratio (m / n) of the half-width (m) of the diffraction peak of the (003) plane to the half-width (n) of the diffraction peak of the (104) plane in an X-ray diffraction pattern based on X-ray diffraction satisfies 0.75 < = m / n < = 1.0.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of an application with a filing date of September 17, 2020, an application number of 202080082480.4, and an invention name of “Positive electrode active material for non-aqueous electrolyte secondary batteries, a method for producing positive electrode active material for non-aqueous electrolyte secondary batteries, and non-aqueous electrolyte secondary batteries”. Technical Field

[0002] The present disclosure relates to a positive electrode active material for a non-aqueous electrolyte secondary battery, a method for producing the positive electrode active material for a non-aqueous electrolyte secondary battery, and a non-aqueous electrolyte secondary battery. Background Art

[0003] In recent years, lithium transition metal composite oxides with high Ni content have attracted much attention as positive electrode active materials with high energy density. For example, Patent Document 1 discloses a positive electrode active material for a non-aqueous electrolyte secondary battery, which comprises a general formula Li x Ni y Co z M m A lithium transition metal composite oxide represented by O2 (wherein M is an element selected from Ba, Sr, and B, 0.9≤x≤1.1, 0.5≤y≤0.95, 0.05≤z≤0.5, 0.0005≤m≤0.02), and having a BET specific surface area value of 0.8m 2 / g or less.

[0004] In addition, Patent Document 2 discloses a positive electrode active material for a non-aqueous electrolyte secondary battery, which has an α-NaFeO2 structure and contains one or more transition metal elements selected from the group consisting of Mn, Ni and Co, and alkaline earth metals and W are present on the particle surface of the lithium transition metal composite oxide.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2003-100295

[0008] Patent Document 2: Japanese Patent Application Publication No. 2018-129221 Summary of the invention

[0009] When a lithium transition metal composite oxide with a high Ni content is used as the positive electrode active material of a non-aqueous electrolyte secondary battery, the amount of Li captured during charging is large, so there is a problem that the layered crystal structure is destroyed and the capacity is reduced due to repeated charge and discharge. It should be noted that the technology disclosed in Patent Documents 1 and 2 still has room for improvement in charge and discharge cycle characteristics.

[0010] A positive electrode active material for a non-aqueous electrolyte secondary battery according to one embodiment of the present disclosure is characterized by comprising: a layered structure having a general formula Li a Ni x Mn y M z O 2-b A lithium transition metal composite oxide represented by (wherein, 0.95<a<1.05, 0.7≤x≤0.95, 0<y≤0.3, 0≤z≤0.3, 0≤b<0.05, x+y+z=1, M is at least one element selected from Al, Co, Fe, Ti, Si, Nb, Mo, W and Zn); and a compound A containing at least one of Ca and Sr present on the surface or grain boundary of the primary particles of the lithium transition metal composite oxide. The layered structure includes a Li layer in which Li reversibly enters and exits, and the ratio of the metal element other than Li present in the Li layer is 0.7 mol% or more and 3.0 mol% or less relative to the total molar amount of the metal element other than Li in the lithium transition metal composite oxide, and the ratio m / n of the half-value width m of the diffraction peak of the (003) plane to the half-value width n of the diffraction peak of the (104) plane in the X-ray diffraction spectrum based on X-ray diffraction is 0.75≤m / n≤1.0.

[0011] A method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery as one embodiment of the present disclosure is characterized by comprising the step of calcining a mixture obtained by dry-mixing at least one of a Ca compound and a Sr compound, a transition metal oxide, and a Li compound at 850° C. or less.

[0012] A nonaqueous electrolyte secondary battery as one embodiment of the present disclosure is characterized by comprising: a positive electrode including the positive electrode active material for a nonaqueous electrolyte secondary battery; a negative electrode; and a nonaqueous electrolyte.

[0013] The positive electrode active material for a non-aqueous electrolyte secondary battery as one embodiment of the present disclosure can provide a high-capacity non-aqueous electrolyte secondary battery that suppresses the decrease in battery capacity accompanying charge and discharge. The positive electrode active material for a non-aqueous electrolyte secondary battery contains a lithium transition metal composite oxide with a high Ni content, which is beneficial for improving the charge and discharge cycle characteristics of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 It is a cross-sectional view of a nonaqueous electrolyte secondary battery as an example of the embodiment.

[0015] Figure 2 These are the X-ray diffraction patterns of Examples 2 and 3 and SrO and CaO.

[0016] Description of Reference Numerals

[0017] 10Non-aqueous electrolyte secondary battery

[0018] 11 Positive electrode

[0019] 12 Negative electrode

[0020] 13 Dividers

[0021] 14 Electrode body

[0022] 15Battery housing

[0023] 16 shell tank

[0024] 17 Sealing body

[0025] 18, 19 insulation board

[0026] 20 positive electrode tabs

[0027] 21 Negative electrode tab

[0028] 22 groove part

[0029] 23 bottom plate

[0030] 24 Lower valve body

[0031] 25 Insulation components

[0032] 26 Upper valve body

[0033] 27 Cover

[0034] 28 gasket

[0035] 30 Positive electrode collector

[0036] 31 positive electrode composite material layer

[0037] 40 negative electrode collector

[0038] 41 negative electrode composite material layer DETAILED DESCRIPTION

[0039] The layered structure of the lithium transition metal composite oxide contained in the positive electrode active material contains a transition metal layer containing Ni, a Li layer, and an oxygen layer. The Li ions present in the Li layer are reversibly released, so that the charge and discharge reaction of the battery proceeds. When using a lithium transition metal composite oxide with a high Ni content, a large amount of Li ions are taken from the Li layer when the battery is charged, so the layered structure collapses, resulting in a decrease in battery capacity. In addition, the activity near the particle surface of the lithium transition metal composite oxide with a high Ni content is high, and the structure is prone to become unstable, so it is easy to cause the generation and erosion of the surface degradation layer through reactions with the electrolyte, etc., resulting in a decrease in battery capacity.

[0040] Therefore, the inventors of the present invention have conducted in-depth research to solve the above-mentioned problems, and found that: first, a predetermined amount of Mn that does not produce an oxidation number change during charge and discharge is contained in the transition metal layer, and a predetermined amount of metal elements other than Li is contained in the Li layer, and then, the ratio of the half-value width m of the (003) plane / the half-value width n of the (104) plane of the X-ray diffraction spectrum is formed to be within a predetermined range, and a layered structure with appropriate strain in the plane direction is formed, so that the structure of the lithium transition metal composite oxide can be maintained and the battery capacity can be improved. Furthermore, the inventors of the present invention have found that the surface of the lithium transition metal composite oxide can be protected by a compound containing at least one of Ca and Sr, so that the corrosion of the structural degradation layer can be suppressed. The lithium transition metal composite oxide with a high Ni content cannot obtain sufficient effects in either the reinforcement of the skeleton of the layered structure or the protection of the surface. By applying both and utilizing their synergistic effect, the charge and discharge cycle characteristics can be specifically improved.

[0041] Hereinafter, an example of an embodiment of the non-aqueous electrolyte secondary battery disclosed in the present invention is described in detail. Hereinafter, a cylindrical battery in which a wound electrode body is housed in a cylindrical battery case is exemplified, but the electrode body is not limited to a wound type, and may also be a stacked type in which a plurality of positive electrodes and a plurality of negative electrodes are alternately stacked one by one through separators. In addition, the battery case is not limited to a cylindrical shape, and may be, for example, a square shape, a coin shape, etc., or may be a battery case composed of a laminated sheet including a metal layer and a resin layer.

[0042] Figure 1 FIG. 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery 10 as an example of an embodiment. Figure 1 As shown in the example, the nonaqueous electrolyte secondary battery 10 includes an electrode body 14, a nonaqueous electrolyte (not shown), and a battery case 15 that accommodates the electrode body 14 and the nonaqueous electrolyte. The electrode body 14 has a winding structure in which a positive electrode 11 and a negative electrode 12 are wound with a separator 13 interposed therebetween. The battery case 15 is composed of an outer shell can 16 in a cylindrical shape with a bottom, and a sealing body 17 that blocks the opening of the outer shell can 16.

[0043] The electrode body 14 is composed of a long positive electrode 11, a long negative electrode 12, two long separators 13, a positive electrode tab 20 joined to the positive electrode 11, and a negative electrode tab 21 joined to the negative electrode 12. In order to prevent the precipitation of lithium, the negative electrode 12 is formed to be one size larger than the positive electrode 11. That is, the negative electrode 12 is formed to be longer than the positive electrode 11 in the length direction and the width direction (short direction). The two separators 13 are formed to be at least one size larger than the positive electrode 11, and are arranged in a manner of sandwiching the positive electrode 11, for example.

[0044] The nonaqueous electrolyte secondary battery 10 includes insulating plates 18 and 19 disposed above and below the electrode body 14 , respectively. Figure 1In the example shown, the positive electrode tab 20 attached to the positive electrode 11 passes through the through hole of the insulating plate 18 and extends to the sealing body 17 side, and the negative electrode tab 21 attached to the negative electrode 12 passes through the outside of the insulating plate 19 and extends to the bottom side of the outer can 16. The positive electrode tab 20 is connected to the lower surface of the bottom plate 23 of the sealing body 17 by welding or the like, and the cover 27 of the sealing body 17 electrically connected to the bottom plate 23 becomes the positive terminal. The negative electrode tab 21 is connected to the bottom inner surface of the outer can 16 by welding or the like, and the outer can 16 becomes the negative terminal.

[0045] The outer shell can 16 is, for example, a metal container in a cylindrical shape with a bottom. A gasket 28 is provided between the outer shell can 16 and the sealing body 17, and the internal space of the battery case 15 is sealed. The outer shell can 16 has, for example, a grooved portion 22 formed by applying pressure to the side surface from the outside to support the sealing body 17. The grooved portion 22 is preferably formed in an annular shape along the circumferential direction of the outer shell can 16, and the sealing body 17 is supported by its upper surface.

[0046] The sealing body 17 has a structure in which a bottom plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26 and a cover 27 are stacked in order from the electrode body 14 side. The components constituting the sealing body 17 have, for example, a disc shape or a ring shape, and the components except the insulating member 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected to each other at their respective central portions, and an insulating member 25 is sandwiched between their respective peripheral portions. When the internal pressure of the battery rises due to abnormal heat release, the lower valve body 24 is deformed and broken in a manner that pushes the upper valve body 26 toward the cover 27 side, and the current path between the lower valve body 24 and the upper valve body 26 is blocked. When the internal pressure rises further, the upper valve body 26 breaks, and gas is discharged from the opening of the cover 27.

[0047] The positive electrode 11 , the negative electrode 12 , the separator 13 , and the nonaqueous electrolyte constituting the nonaqueous electrolyte secondary battery 10 , particularly the positive electrode active material contained in the positive electrode composite material layer 31 constituting the positive electrode 11 , will be described in detail below.

[0048] [positive electrode]

[0049] The positive electrode 11 has: a positive electrode collector 30, and a positive electrode composite material layer 31 formed on both sides of the positive electrode collector 30. The positive electrode collector 30 can use a foil of a metal such as aluminum or aluminum alloy that is stable within the potential range of the positive electrode 11, a thin film of the metal configured on the surface, etc. The positive electrode composite material layer 31 contains: a positive electrode active material, a conductive material, and a binding material. The thickness of the positive electrode composite material layer 31 is, for example, 10 μm to 150 μm on one side of the positive electrode collector 30. The positive electrode 11 can be made as follows: a positive electrode slurry containing a positive electrode active material, a conductive material, and a binding material is applied to the surface of the positive electrode collector 30, and after the coating is dried, it is compressed to form a positive electrode composite material layer 31 on both sides of the positive electrode collector 30, thereby making it.

[0050] As the conductive material contained in the positive electrode composite material layer 31, carbon materials such as carbon black, acetylene black, Ketjen black, and graphite can be exemplified. As the binding material contained in the positive electrode composite material layer 31, fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide, acrylic resin, polyolefin, etc. can be exemplified. These resins can be used in combination with carboxymethyl cellulose (CMC) or its salt, polyethylene oxide (PEO), etc.

[0051] The positive electrode active material contained in the positive electrode composite material layer 31 includes: a lithium transition metal composite oxide having a layered structure; and a compound A containing at least one of Ca and Sr existing on the primary particle surface or grain boundary of the secondary particle surface containing the lithium transition metal composite oxide.

[0052] The layered structure of the lithium transition metal composite oxide includes, for example, a layered structure belonging to the space group R-3m, a layered structure belonging to the space group C2 / m, etc. Among them, from the perspective of high capacity, stability of the crystal structure, etc., the layered structure belonging to the space group R-3m is preferred. The layered structure of the lithium transition metal composite oxide includes a transition metal layer, a Li layer, and an oxygen layer.

[0053] Lithium transition metal composite oxides can be represented by the general formula Li a Ni x Mn y M z O 2-b (wherein, 0.95<a<1.05, 0.7≤x≤0.95, 0<y≤0.3, 0≤z≤0.3, 0≤b<0.05, x+y+z=1, M is at least one element selected from Al, Co, Fe, Ti, Si, Nb, Mo, W and Zn). It should be noted that the positive electrode active material may contain lithium transition metal composite oxides or other compounds other than those shown in the above general formula within the scope that does not impair the purpose of the present disclosure. The molar fraction of the metal elements contained in the lithium transition metal composite oxide can be measured using an inductively coupled plasma emission spectrophotometer (ICP-AES), an electron beam microanalyzer (EPMA), an energy dispersive X-ray analyzer (EDX), etc.

[0054] a, which represents the ratio of Li in the lithium transition metal composite oxide, satisfies 0.95≤a<1.05, and preferably satisfies 0.97≤a≤1.03. When a is less than 0.95, the battery capacity may be reduced compared with the case where a satisfies the above range. When a is 1.05 or more, the charge-discharge cycle characteristics may be reduced compared with the case where a satisfies the above range.

[0055] The ratio x of Ni to the total molar number of metal elements other than Li in the lithium transition metal composite oxide satisfies 0.7≤x≤0.95, preferably satisfies 0.8≤x≤0.95. By making x greater than 0.7, a high-capacity battery can be obtained. In addition, when x is greater than 0.8, it is easy to obtain the effect of improving the cycle characteristics caused by the stabilization of the structure of the lithium transition metal composite oxide. In addition, when x exceeds 0.95, it is impossible to contain sufficient amounts of Mn and M, so the layered structure of the lithium transition metal composite oxide becomes unstable.

[0056] The content y representing the Mn content relative to the total molar number of metal elements other than Li in the lithium transition metal composite oxide preferably satisfies 0<y≤0.3, and more preferably satisfies 0.01≤y≤0.15. Mn does not change its oxidation number during charge and discharge, so it is believed that by containing it in the transition metal layer, the structure of the transition metal layer is stabilized. On the other hand, when y exceeds 0.3, the content of Ni decreases and the battery capacity decreases. Mn can be uniformly dispersed in the layered structure of the lithium transition metal composite oxide, or it can be present in a part of the layered structure.

[0057] M (M is at least one element selected from Al, Co, Fe, Ti, Si, Nb, Mo, W and Zn) is an arbitrary component. z, which represents the content of M relative to the total number of moles of metal elements other than Li in the lithium transition metal composite oxide, preferably satisfies 0≤z≤0.3.

[0058] The lithium transition metal composite oxide is a particle having a volume-based median particle size (D50) of, for example, 3 μm to 30 μm, preferably 5 μm to 25 μm, and particularly preferably 7 μm to 15 μm. D50 refers to the particle size at which the cumulative frequency of the particle size distribution based on the volume becomes 50% from the particle with the smallest particle size, and is also called the median diameter. The particle size distribution of the lithium transition metal composite oxide can be measured using a laser diffraction particle size distribution measuring device (e.g., MicrotracBEL Corp., MT3000II) using water as a dispersion medium.

[0059] The lithium transition metal composite oxide is, for example, a secondary particle formed by agglomeration of a plurality of primary particles. The particle size of the primary particles constituting the secondary particles is, for example, 0.05 μm to 1 μm. The particle size of the primary particles is measured as the diameter of the circumscribed circle of the particle image observed by a scanning electron microscope (SEM).

[0060] Compound A is present on the surface or grain boundary of the primary particles of the lithium transition metal composite oxide. Thus, the formation and erosion of the structural degradation layer on the surface of the lithium transition metal composite oxide produced by the reaction with the electrolyte, etc. can be suppressed. Here, the surface of the primary particle includes the surface of the secondary particle. In addition, the grain boundary of the primary particle refers to the interface between the primary particles. The presence of compound A on the surface or grain boundary of the primary particle refers to a state of contact with the surface or grain boundary of the primary particle, or a state of being located within a range of 10nm or less from the surface or grain boundary of the primary particle. Compound A can be uniformly dispersed on the entire surface and interface of the lithium transition metal composite oxide, or can be present in a part.

[0061] Compound A contains at least one of Ca and Sr. Compound A may contain a Ca compound or an Sr compound. Examples of Ca compounds include CaO, Ca(OH)2, and CaCO3. Examples of Sr compounds include SrO, Sr(OH)2, and SrCO3.

[0062] The total amount of Ca and Sr in the compound A may be 1 mol% or less relative to the total molar amount of metal elements other than Li in the lithium transition metal composite oxide. Thus, the charge-discharge cycle characteristics can be further improved.

[0063] The layered structure of the lithium transition metal composite oxide includes a Li layer in which Li reversibly enters and exits, and the proportion of metal elements other than Li present in the Li layer is greater than 0.7 mol% and less than 3.0 mol% relative to the total molar amount of metal elements other than Li in the lithium transition metal composite oxide. When the proportion of metal elements other than Li in the Li layer is less than 0.7 mol%, the stability of the layered structure in the state where Li ions in the Li layer are captured is reduced, and the structure is destroyed, resulting in a reduction in battery capacity. In addition, when the proportion of metal elements other than Li in the Li layer exceeds 3.0 mol%, the diffusivity of Li ions in the Li layer is reduced, the battery capacity is reduced, and the reaction resistance of the battery becomes higher. The metal elements present in the Li layer are mainly Ni, but other metal elements may also be included.

[0064] The ratio of metal elements other than Li in the Li layer is obtained from the Rietveld analysis result of the X-ray diffraction spectrum of the positive electrode active material by X-ray diffraction measurement. For example, PDXL2 (Rigaku Co., Ltd.), which is Rietveld analysis software, can be used for the Rietveld analysis of the X-ray diffraction spectrum.

[0065] The X-ray diffraction spectrum was obtained by powder X-ray diffraction under the following conditions using a powder X-ray diffractometer (manufactured by Rigaku Co., Ltd., trade name “RINT-TTR”, radiation source Cu—Kα).

[0066] Measuring range: 15-120°

[0067] Scanning speed: 4° / min

[0068] Analysis range: 30-120°

[0069] Background: B-spline

[0070] Profile function: segmented pseudo-Voigt function

[0071] Binding condition: Li(3a)+Ni(3a)=1

[0072] Ni(3a)+Ni(3b)=α (α is the content ratio of each Ni)

[0073] ICSD No.:98-009-4814

[0074] For the positive electrode active material, the crystallite size s calculated from the half-value width n of the diffraction peak on the (104) plane of the X-ray diffraction spectrum based on the above X-ray diffraction and the Scherrer equation is preferably The crystallite size s of the lithium transition metal composite oxide is less than In the case of , the crystallinity is reduced, sometimes resulting in a reduction in battery capacity. In addition, the crystallite size s of the lithium transition metal composite oxide exceeds In the case of , the diffusion of Li deteriorates, and the power characteristics of the battery may decrease. The Scherrer equation is as follows.

[0075] s=Kλ / Bcosθ

[0076] In the above formula, s is the crystallite size, λ is the wavelength of X-rays, B is the half-value width of the diffraction peak of the (104) plane, θ is the diffraction angle (rad), and K is the Scherrer constant. In this embodiment, K is set to 0.9.

[0077] For the positive electrode active material, the ratio m / n of the half-width m of the diffraction peak of the (003) surface of the X-ray diffraction spectrum based on the above-mentioned X-ray diffraction relative to the half-width n of the diffraction peak of the (104) surface is 0.75≤m / n≤1.0. If it is in this range, a state in which the layered structure has a moderate strain in the plane direction can be formed, so a battery with high capacity and improved charge and discharge cycle characteristics can be obtained. When m / n is less than 0.75, the strain of the layered structure is excessively large, and the layered structure becomes brittle. In addition, when m / n exceeds 1.0, the battery capacity is reduced.

[0078] The positive electrode active material preferably does not have peaks derived from CaO and SrO in the X-ray diffraction spectrum obtained by the X-ray diffraction measurement. If CaO and SrO are contained to a degree detectable by the X-ray diffraction measurement, the battery capacity may be reduced.

[0079] Next, an example of a method for producing a positive electrode active material including a lithium transition metal composite oxide and compound A is described.

[0080] The method for producing a positive electrode active material includes, for example, a first step of obtaining a transition metal oxide containing Ni, Mn and an arbitrary metal element; a second step of mixing the transition metal oxide obtained in the first step with a Li compound to obtain a mixture; and a third step of calcining the mixture.

[0081] In the first step, for example, a solution of a metal salt containing Ni, Mn and any metal element (Co, Al, Nb, etc.) is stirred while an alkaline solution such as sodium hydroxide is added dropwise to adjust the pH to the alkaline side (e.g., 8.5 to 12.5), thereby precipitating (coprecipitating) a transition metal hydroxide containing Ni, Mn and any metal element, and calcining the transition metal hydroxide to obtain a transition metal oxide containing Ni, Mn and any metal element. The calcination temperature is not particularly limited, and is, for example, in the range of 300° C. to 600° C.

[0082] In the second step, at least one of the Ca compound and the Sr compound, the transition metal oxide obtained in the first step, and the Li compound are dry-mixed to obtain a mixture. Examples of the Li compound include Li2CO3, LiOH, Li2O2, Li2O, LiNO3, LiNO2, Li2SO4, LiOH·H2O, LiH, and LiF. Examples of the Ca compound include Ca(OH)2, CaO, CaCO3, CaSO4, and Ca(NO3)2. Examples of the Sr compound include Sr(OH)2, Sr(OH)2·8H2O, SrO, SrCO3, SrSO4, and Sr(NO3)2. As for the mixing ratio of the transition metal oxide obtained in the first step and the Li compound, it is preferred that the molar ratio of the metal element other than Li:Li be in the range of 1:0.98 to 1:1.1, from the perspective of facilitating the adjustment of the above parameters to the above-defined ranges. In addition, for the mixing ratio of the transition metal oxide obtained in the first step and the Ca compound or the Sr compound, from the perspective of facilitating the adjustment of the above parameters to the above-defined ranges, for example, it is preferably set to a ratio in the range of 1:0.0003 to 1:0.03 in which the molar ratio of the metal element other than Li:Ca and Sr is. In the second step, when the transition metal oxide obtained in the first step is mixed with the Li compound and the Ca compound or the Sr compound, other metal raw materials may be added as needed. Other metal raw materials are oxides of metal elements other than the metal elements constituting the transition metal oxide obtained in the first step, etc.

[0083] In the third step, the mixture obtained in the second step is calcined at a temperature below 850°C for a predetermined time to obtain the positive electrode active material of the present embodiment. If the calcination is performed at a temperature exceeding 850°C, the compound A containing at least one of Ca and Sr is aggregated in a specific part, and sometimes a sufficient effect cannot be obtained. The calcination of the mixture in the third step, for example, has a multi-stage calcination process, and the multi-stage calcination process includes the following steps: a first calcination process, calcining in a calcination furnace, under an oxygen gas flow, at a first heating rate until a first set temperature of 450°C to 680°C; and a second calcination process, calcining the calcined product obtained by the first calcination process in a calcination furnace, under an oxygen gas flow, at a second heating rate until a second set temperature exceeding 680°C and below 850°C. Here, the first heating rate is in the range of 1.5°C / min to 5.5°C / min, and the second heating rate is slower than the first heating rate, and is in the range of 0.1°C / min to 3.5°C / min. It should be noted that if the first heating rate and the second heating rate are within the above-defined range, multiple heating rates can be set in each temperature zone. From the perspective of adjusting the above-mentioned parameters of the lithium transition metal composite oxide to the above-defined range, the holding time of the first set temperature in the first roasting process is preferably less than 5 hours, and more preferably less than 3 hours. The holding time of the first set temperature refers to the time for maintaining the first set temperature after reaching the first set temperature. From the perspective of adjusting the above-mentioned parameters of the lithium transition metal composite oxide to the above-defined range, the holding time of the second set temperature in the second roasting process is preferably 1 hour to 10 hours, and more preferably 1 hour to 5 hours. The holding time of the second set temperature refers to the time for maintaining the second set temperature after reaching the second set temperature. When the mixture is roasted, from the perspective of adjusting the above-mentioned parameters to the above-defined range, for example, it can be carried out in an oxygen gas flow with an oxygen concentration of more than 60%, and the flow rate of the oxygen gas flow is set to 100% per 10cm 3 The calcination furnace is in the range of 0.2 mL / min to 4 mL / min and is 0.3 L / min or more per 1 kg of the mixture.

[0084] The molar fraction of the metal element contained in the positive electrode active material obtained above was measured by inductively coupled plasma (ICP) emission spectrophotometry and can be expressed by the general formula Li a Ni x Mn y M z Ca α Sr β O 2-b(wherein, 0.95<a<1.05, 0.7≤x≤0.95, 0<y≤0.3, 0≤z≤0.3, α+β>0, 0≤b<0.05, x+y+z=1, M is at least one element selected from Al, Co, Fe, Ti, Si, Nb, Mo, W and Zn). It should be noted that Ca and Sr are contained in the compound A present on the surface of the lithium transition metal composite oxide.

[0085] [negative electrode]

[0086] The negative electrode 12 has: a negative electrode collector 40, and a negative electrode composite material layer 41 formed on both sides of the negative electrode collector 40. The negative electrode collector 40 may be made of a foil of a metal such as copper or a copper alloy that is stable within the potential range of the negative electrode 12, or a thin film having the metal disposed on the surface. The negative electrode composite material layer 41 contains a negative electrode active material and a binding material. The thickness of the negative electrode composite material layer 41 is, for example, 10 μm to 150 μm on one side of the negative electrode collector 40. The negative electrode 12 can be made as follows: a negative electrode composite material slurry containing a negative electrode active material, a binding material, etc. is applied to the surface of the negative electrode collector 40, and the coating is dried and then rolled to form a negative electrode composite material layer 41 on both sides of the negative electrode collector 40, thereby making it.

[0087] The negative electrode active material contained in the negative electrode composite material layer 41 is not particularly limited as long as it can reversibly absorb and release lithium ions, and carbon materials such as graphite are generally used. The graphite may be natural graphite such as flaky graphite, blocky graphite, and earthy graphite, blocky artificial graphite, and artificial graphite such as graphitized mesophase carbon microbeads. In addition, as the negative electrode active material, metals such as Si and Sn alloyed with Li, metal compounds containing Si, Sn, etc., lithium-titanium composite oxides, etc. can be used. In addition, those provided with a carbon coating on them can also be used. For example, SiO x (0.5≤x≤1.6) represented by a Si-containing compound, or Li 2y SiO (2+y) A Si-containing compound in which Si fine particles are dispersed in a lithium silicate phase represented by (0<y<2) or the like can be used together with graphite.

[0088] The binder contained in the negative electrode composite material layer 41 may be a fluorine-containing resin such as PTFE and PVdF, PAN, polyimide, acrylic resin, polyolefin, etc., as in the case of the positive electrode 11, preferably styrene-butadiene rubber (SBR). In addition, the negative electrode composite material layer 41 may contain CMC or its salt, polyacrylic acid (PAA) or its salt, polyvinyl alcohol (PVA), etc.

[0089] [Separator]

[0090] For example, a porous sheet having ion permeability and insulation can be used as the separator 13. Specific examples of the porous sheet include microporous films, woven fabrics, non-woven fabrics, etc. As the material of the separator 13, polyolefins such as polyethylene and polypropylene, cellulose, etc. are ideal. The separator 13 can have a single-layer structure or a laminated structure. In addition, a resin layer with high heat resistance such as aramid resin or a filler layer containing a filler of an inorganic compound can be provided on the surface of the separator 13.

[0091] [Non-aqueous electrolyte]

[0092] The non-aqueous electrolyte includes, for example, a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. For example, esters, ethers, nitriles such as acetonitrile, amides such as dimethylformamide, and mixed solvents of two or more thereof can be used in the non-aqueous solvent. The non-aqueous solvent may contain a halogen substituted body formed by replacing at least a portion of the hydrogen of these solvents with a halogen atom such as fluorine. As the halogen substituted body, fluorinated cyclic carbonates such as fluorinated ethylene carbonate (FEC), fluorinated chain carbonates, fluorinated chain carboxylates such as methyl fluoropropionate (FMP), etc. can be cited.

[0093] Examples of the above-mentioned esters include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate, chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, and methyl isopropyl carbonate, cyclic carboxylates such as γ-butyrolactone (GBL) and γ-valerolactone (GVL), and chain carboxylates such as methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), and ethyl propionate (EP).

[0094] Examples of the ethers include 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-butylene oxide, 1,3-dioxane, 1,4-dioxane, 1,3,5-trioxane, furan, 2-methylfuran, 1,8-cineole, cyclic ethers such as crown ethers, 1,2-dimethoxyethane, ethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, dihexyl ether, Ethyl vinyl ether, butyl vinyl ether, methyl phenyl ether, ethyl phenyl ether, butyl phenyl ether, pentyl phenyl ether, methoxytoluene, benzyl ethyl ether, diphenyl ether, dibenzyl ether, o-dimethoxybenzene, 1,2-diethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether and other chain ethers, etc.

[0095] The electrolyte salt is preferably a lithium salt. Examples of lithium salts include LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiMnCl4, LiSCN, LiCF3SO3, LiCF3CO2, Li(P(C2O4)F4), LiPF 6-x (C n F 2n+1 ) x (1<x<6, n is 1 or 2), LiB 10 Cl 10 , LiCl, LiBr, LiI, lithium chloroborane, lower aliphatic carboxylic acid lithium, Li2B4O7, Li(B(C2O4)F2) and other borates, LiN(SO2CF3)2, LiN(C1F 2l+1 SO2)(C m F 2m+1 SO2) {l, m is an integer greater than 0} and other imide salts. The lithium salt can be used alone or in combination. Among them, LiPF6 is preferably used from the viewpoint of ion conductivity, electrochemical stability, etc. The concentration of the lithium salt is, for example, 0.8 mol to 1.8 mol per 1L of non-aqueous solvent. In addition, vinylene carbonate and propane sultone additives can be further added.

[0096] <Example>

[0097] Hereinafter, the present disclosure will be further described by way of Examples and Comparative Examples, but the present disclosure is not limited to the following Examples.

[0098] [Preparation of positive electrode active material]

[0099] <Example 1>

[0100] Relative to the general formula Ni 0.82 Mn 0.03 Co 0.15 The transition metal oxide represented by O2 is mixed with Sr(OH)2 and Ca(OH)2 in such a manner that the total amount of Ni, Mn and Co, and the content of Sr and Ca are 1.0 mol% and 0.1 mol%, respectively. Lithium hydroxide monohydrate (LiOH·H2O) is further mixed in such a manner that the molar ratio of the total amount of Ni, Mn, Co, Sr and Ca to Li is 1:1.03. The mixture is calcined from room temperature to 650°C at a heating rate of 2°C / min under an oxygen gas flow with an oxygen concentration of 95% (a flow rate of 5 L / min per 1 kg of the mixture), and then calcined from 650°C to 800°C at a heating rate of 1°C / min. The calcined product is washed with water to remove impurities, thereby obtaining the positive electrode active material of Example 1. The composition of the positive electrode active material of Example 1 was analyzed by ICP-AES, and the result was Li0.99 Ni 0.82 Mn 0.03 Co 0.15 Sr 0.01 Ca 0.001 O2. In addition, X-ray diffraction measurement was performed on the positive electrode active material of Example 1. The ratio of the total molar amount of the metal elements other than Li present in the Li layer to the total molar amount of the metal elements other than Li in the lithium transition metal composite oxide was 0.87 mol%. The ratio m / n of the half-value width m of the diffraction peak of the (003) plane of the X-ray diffraction spectrum based on X-ray diffraction to the half-value width n of the diffraction peak of the (104) plane was 0.978.

[0101] [Production of positive electrode]

[0102] The positive electrode active material is mixed in a ratio of 95 parts by mass, acetylene black as a conductive material is mixed in a ratio of 3 parts by mass, and polyvinylidene fluoride as a binding material is mixed in a ratio of 2 parts by mass, and mixed with N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode slurry. Next, the slurry is applied to a positive electrode collector formed of an aluminum foil having a thickness of 15 μm, and after the coating is dried, the coating is rolled by a rolling roller and cut into a specified electrode size to obtain a positive electrode having a positive electrode composite material layer formed on both sides of the positive electrode core. It should be noted that an exposed portion exposed on the surface of the positive electrode core is provided on a portion of the positive electrode.

[0103] [Preparation of non-aqueous electrolyte]

[0104] Ethylene carbonate (EC), ethyl methyl carbonate (MEC), and dimethyl carbonate (DMC) were mixed at a volume ratio of 3:3:4. Lithium hexafluorophosphate (LiPF6) was dissolved in the mixed solvent to a concentration of 1.2 mol / L to prepare a non-aqueous electrolyte.

[0105] [Production of test battery cells]

[0106] An aluminum lead was installed on the exposed portion of the positive electrode, and a nickel lead was installed on the lithium metal foil as the negative electrode. The positive electrode and the negative electrode were spirally wound with a polyolefin separator interposed therebetween, and then press-formed in the radial direction to produce a flat wound electrode body. The electrode body was housed in an outer shell composed of an aluminum laminate sheet, and after the non-aqueous electrolyte was injected, the opening of the outer shell was sealed to obtain a test battery cell.

[0107] [Evaluation of capacity maintenance rate]

[0108] The test battery cell was subjected to the following cycle test. The discharge capacity at the first cycle and the discharge capacity at the 30th cycle of the cycle test were obtained, and the capacity retention rate was calculated according to the following formula.

[0109] Capacity retention rate (%) = (30th cycle discharge capacity ÷ 1st cycle discharge capacity) × 100

[0110] <Cyclic test>

[0111] The test battery cell was charged at a constant current of 0.2 It until the battery voltage reached 4.3 V, and then charged at a constant voltage of 4.3 V until the current value reached 1 / 100 It. Thereafter, the battery cell was discharged at a constant current of 0.2 It until the battery voltage reached 2.5 V. This charge and discharge cycle was repeated 30 times.

[0112] <Examples 2 and 4>

[0113] The raw materials used and the raw material mixing ratio were changed, the molar ratio of the total amount of metal elements other than Li to Li was changed to 1:1.05, and the second stage calcination temperature was changed to 750°C to synthesize the positive electrode active material. Except for this, test battery cells were prepared and evaluated in the same manner as in Example 1.

[0114] <Example 3>

[0115] Test cells were prepared and evaluated in the same manner as in Example 4 except that the raw material mixing ratio was changed and the positive electrode active material was synthesized under oxygen gas flow with an oxygen concentration of 95% (flow rate of 10 L / min per 1 kg of the mixture).

[0116] <Example 5>

[0117] The positive electrode active material was synthesized by changing the raw materials used, the raw material mixing ratio, and the calcination from room temperature to 650°C at a heating rate of 5°C / min and then from 650°C to 750°C at a heating rate of 3°C / min. Except for this, test battery cells were prepared and evaluated in the same manner as in Example 2.

[0118] <Examples 6 to 8>

[0119] Test cells were prepared and evaluated in the same manner as in Example 1 except that the raw materials used and the raw material mixing ratio were changed and the second-stage calcination temperature was changed to 730° C. to synthesize the positive electrode active material.

[0120] <Comparative Example 1>

[0121] Test cells were prepared and evaluated in the same manner as in Example 1 except that the raw material mixing ratio was changed to synthesize the positive electrode active material.

[0122] <Comparative Example 2>

[0123] Except for changing the raw materials used and the raw material mixing ratio to synthesize the positive electrode active material, test cells were prepared and evaluated in the same manner as in Example 2.

[0124] <Comparative Example 3>

[0125] Test battery cells were prepared and evaluated in the same manner as in Example 2 except that the raw material mixing ratio was changed, the molar ratio of the total amount of metal elements other than Li to Li was changed to 1:0.95, and the second-stage calcination temperature was changed to 850°C to synthesize the positive electrode active material.

[0126] <Comparative Example 4>

[0127] Test cells were prepared and evaluated in the same manner as in Example 2 except that the raw materials and raw material mixing ratios were changed and the positive electrode active material was synthesized under an oxygen gas flow with an oxygen concentration of 95% (flow rate of 0.1 L / min per 1 kg of the mixture).

[0128] <Comparative Example 5>

[0129] Except for changing the raw materials used and the raw material mixing ratio to synthesize the positive electrode active material, test cells were prepared and evaluated in the same manner as in Example 6.

[0130] <Comparative Example 6>

[0131] Test cells were prepared and evaluated in the same manner as in Example 1 except that the raw materials used and the raw material mixing ratio were changed and the second-stage calcination temperature was changed to 730° C. to synthesize the positive electrode active material.

[0132] <Comparative Example 7>

[0133] Test cells were prepared and evaluated in the same manner as in Example 7 except that the raw material mixing ratio was changed and the molar ratio of the total amount of metal elements other than Li to Li was changed to 1:1.1 to synthesize the positive electrode active material.

[0134] The capacity retention rates of the embodiments and comparative examples are shown in Tables 1 to 3. The evaluation results of the capacity retention rates shown in Tables 1 to 3 are relatively expressed with the capacity retention rates of the test battery cells of Comparative Examples 1, 2, and 5 being 100%. In addition, Tables 1 to 3 also show the ratio m / n of the half-value width m of the diffraction peak of the (003) plane to the half-value width n of the diffraction peak of the (104) plane in the X-ray diffraction spectrum based on X-ray diffraction, and the ratio of the metal elements other than Li present in the Li layer to the total number of moles of the metal elements other than Li.

[0135] [Table 1]

[0136]

[0137] [Table 2]

[0138]

[0139] [Table 3]

[0140]

[0141] As shown in Tables 1 to 3, Examples 1 to 8 have higher capacity retention rates than Comparative Examples 1 to 7. It should be noted that for any of the Examples, there are no peaks derived from SrO and CaO in the X-ray diffraction spectrum. As an example, Figure 2 The X-ray diffraction patterns of Examples 2 and 3 and SrO and CaO are shown in FIG.

Claims

1. A positive electrode active material for a non-aqueous electrolyte secondary battery, comprising: With layered structure, general formula Li a Ni x Mn y M z O 2-b The lithium transition metal composite oxide shown in the formula, wherein 0.95<a<1.05, 0.7≤x≤0.95, 0<y≤0.3, 0≤z≤0.3, 0≤b<0.05, x+y+z=1, and M is at least one element selected from Al, Co, Si, and Nb; and a compound A containing at least one of Ca and Sr and existing on the surface or grain boundary of the primary particles of the lithium transition metal composite oxide, The layered structure includes a Li layer in which Li can be reversibly introduced and withdrawn, and a ratio of a metal element other than Li present in the Li layer is 0.7 mol% or more and 3.0 mol% or less relative to a total molar amount of the metal element other than Li in the lithium transition metal composite oxide, The total amount of Ca and Sr in the compound A is 1 mol % or less relative to the total molar amount of metal elements other than Li in the lithium transition metal composite oxide.

2. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein In the X-ray diffraction spectrum obtained by X-ray diffraction measurement, there are no peaks derived from CaO and SrO.

3. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein The crystallite size s calculated from the half-value width n of the diffraction peak on the (104) plane of the X-ray diffraction spectrum based on X-ray diffraction and the Scherrer formula is: range.

4. A method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 3, comprising the following steps: A mixture in which at least one of a Ca compound and a Sr compound, a transition metal oxide, and a Li compound are dry-mixed is calcined at 850° C. or less. 5 . A non-aqueous electrolyte secondary battery comprising: a positive electrode comprising the positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 ; a negative electrode; and a non-aqueous electrolyte.

Citation Information

Patent Citations

  • Positive electrode material for lithium secondary battery and manufacturing method thereof

    JP2003100295A

  • Positive electrode active material for nonaqueous electrolyte secondary battery and method for manufacturing the same, positive electrode for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery

    JP2018129221A